The Effect of Quercetin and Hyperthermia on spheroid model of DU145 Prostate Carcinoma Cell line - Khoei, Samideh; Azarian, Maryam; Rafipour, Maryam (Archives of Advances in Biosciences, 2013)
The purpose of this study is to investigate the effects of Quercetin as an inhibitor of heat shock proteins and hyperthermia on the induced DNA damages and colony formation ability of DU145 tumor spheroid culture. DU145 cells were cultured as spheroids. On day11, spheroids with mean diameter 100 μm were treated with different concentration of Quercetin for 24 hours and then exposed to hyperthermia at 43oC for 1 hour. After heat exposure, the colony forming ability and the induced DNA damages were examined using colonogenic and alkaline comet assay methods, respectively. Our results showed that DMSO diluent in combination with hyperthermia had no significant effect on the number of colonies and the level of DNA damages as compared to control (p>0.05). Furthermore, number of colonies decreased and DNA damages increased by increasing Quercetin concentration in combined treatment of DU145 cells with Quercetin and hyperthermia in spheroid cultures. Quercetin as an inhibitor of heat shock protein 70 production in cells exposed to hyperthermia can increase DNA damages and decrease colony numbers of the prostate cancer cells in a dose-dependent manner and there is a correlation between the increase of DNA damages and decrease of colony numbers.